Photoacoustic study of silica-silane coupling reagent interactions - Abu-Zeid, M.E; Mahmoud Ahmed, Gharib Subhi; Anani , A. A.; Halasa, A. F.; Mobasher, A. A. (Elsevier, 1981)
Photoacoustic spectroscopy is an effective technique for studying fillercoupling reagent interactions. The use of coupling agents with inorganic fillers necessitates a thorough understanding of the binding activity that takes place. The binding of vinyltriethoxysilane to the hydroxyl groups on a silica surface was identified. Whereas the visible part of the photoacoustic spectra revealed that strong binding took place, the near IR characterized the surface binding groups.